Adsorption of chain molecules in pores with crystalline walls: a density functional approach - Bucior, K.; Patrykiejew, A.; Sokołowski, S.; Pizio, O. (Condensed Matter Physics, 2009)
A microscopic density functional theory of adsorption of chain molecules on the attractive solid surfaces of
crystalline symmetry is developed. The proposed approach is based on the expansions of one-particle functions
into two-dimensional Fourier series. Illustrative calculations for dimers, 8- and 16-mers adsorbed on a
(100) fcc crystal surface indicate the effect of the periodicity of the adsorbing potential on the structure of the
adsorbed layer and thermodynamics of adsorption. Розвинуто мiкроскопiчну теорiю функцiоналу густини для вивчення адсорбцiї ланцюгових молекул на притягальних твердих поверхнях кристалiчної симетрiї. Запропонований пiдхiд ґрунтується на розкладах одночастинкових функцiй у двовимiрнi ряди Фур’є. Для iлюстрацiї проведено обчислення для димерiв, 8- i 16-мерiв, що адсорбованi на кристалiчнiй поверхнi (100) fcc, якi демонструють вплив перiодичностi адсорбуючого потенцiалу на структуру адсорбованого шару i термодинамiку адсорбцiї.